Investigating the flow of information during speaking: the impact of morpho-phonological, associative, and categorical picture distractors on picture naming - Bölte, Jens; Böhl, Andrea; Dobel, Christian; Zwitserlood, Pienie (Frontiers in Psychology, 2015)
In three experiments, participants named target pictures by means of German compound words (e.g., Gartenstuhl - garden chair), each accompanied by two different distractor pictures (e.g., lawn mower and swimming pool).Targets and distractor pictures were semantically related, either associatively (garden chair and lawn mower) or by a shared semantic category (garden chair and wardrobe). Within each type of semantic relation, target and distractor pictures either shared morpho-phonological (word-form) information (Gartenstuhl with Gartenzwerg, garden gnome, and Gartenschlauch, garden hose) or not. A condition with two completely unrelated pictures served as baseline. Target naming was facilitated when distractor and target pictures were morpho-phonologically related. This is clear evidence for the activation of lexical information of distractor pictures. Effects were larger for associatively than for categorically related distractors and targets, which constitutes evidence for lexical competition. Mere categorical relatedness, in the absence of morpho-phonological overlap, resulted in null effects (Experiments 1 and 2), and only speeded target naming when effects reflect only conceptual, not lexical processing (Experiment 3). Given that distractor pictures activate their word forms, the data cannot be easily reconciled with discrete serial models. The results fit well with models that allow information to cascade forward from conceptual to word-form levels.